ANALISIS EFISIENSI ENERGI FLOW BATERAI LEAD ACID KEADAAN STATIS DAN DINAMIS - Muhammad Ghufron; Pranata Budi Kurriawan; Istiroyah Istiroyah; Perwita Anik Cholisina (ROTOR, 2017)
Charging-discharging research was conducted on Redox Flow battery (RFB) using Pb as cathode, PbO as anode, and H2SO4 solution as electrolyte. The research was done by using static and dynamic methode. The experimental shows that RFB was succesfully created and show secondary battery characteristic (charge and discharge graph). According to the charge-discharge characteristic for 5 cycles RFB, shows that the RFB capacity is 1800 mAh when RFB on the static mode while RFB in dynamic mode, the capacity is 2900 mAh. Based on the graph, it was found that the energy efficiency of RFB in the static mode is 50,1% and 71,1% for dynamic mode. Keywords: Charging, discharging, RFB, Energy eficiency